Potentiality in the application of polymeric complexes in plant extract of babassu coconut (Orbignya sp.) - Rocha, Lindalva de Moura; Araújo, Wesley Fernandes; de Paula, Gabriela Almeida; Junior, José Ribeiro dos Santos (Seven Editora, 2023)
The objective was to conduct a technological and bibliographic survey regarding the application of polymeric materials in the development of products based on the vegetable extract water-soluble powder of babassu coconut (Orbignya sp). The databases of the PTO, EPO, USPTO, and WIPO were searched for the survey of patents and the databases of SciELO, Scopus, and Web of Science journals were searched for articles. Forty-six patients were found, but only two of them that were listed in the Subclass A23L of the International Patent Classification (food products or non-alcoholic beverages, their preparation or treatment), but none were related to the production of vegetable milk, let alone the application of a polymer in the process. With researched articles, it was observed that even though patent records are not found, there are studies that have already addressed the elaboration of vegetable extract powder based on the use of babassu almonds, mainly bringing to light the use of polymers in their methodologies, such as maltodextrin as a way to optimize drying by milk spray, gum as an encapsulating agent. The application of these polymers is promising if combined correctly in the formulation of the vegetable extract water-soluble powder of babassu coconut. DOI: https://doi.org/10.56238/devopinterscie-031